2009
DOI: 10.1007/s11249-009-9553-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant Oligomerization Degree on Lubricant Properties of Mixed Surfactant-Diblock Copolymer Films

Abstract: In this study, we investigate the coadsorption and the behavior under shear of mixtures of an anionicneutral hydrophilic-hydrophilic diblock copolymer and oligomeric cationic surfactants on mica surfaces. Three different ammonium quaternary oligomeric surfactants are studied: a monomer, a gemini, and a trimer. Using both an Atomic Force Microscope (AFM) and a Surface Force Apparatus modified for nanotribology studies (SFA-N), we compare the morphology, the interactions between two coated surfaces, and the fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It was significantly enhanced by the poly(acrylic acid)-poly(acrylamide) diblock copolymer for the cationic trimeric and dimeric surfactants with C12 hydrocarbon chains and C3 spacers, whereas layers composed of the monomeric surfactant cetylammonium chloride and the co-polymer did not display a high load bearing capacity. 44 We also note that the load bearing capacity of lubricin was significantly higher on COMP-coated PMMA compared to when lubricin was adsorbed directly on PMMA (see Fig. 8), whereas layer-by-layer deposition of DPPC and hyaluronan reduced the load bearing capacity compared to DPPC alone.…”
Section: Load Bearing Capacitymentioning
confidence: 61%
See 1 more Smart Citation
“…It was significantly enhanced by the poly(acrylic acid)-poly(acrylamide) diblock copolymer for the cationic trimeric and dimeric surfactants with C12 hydrocarbon chains and C3 spacers, whereas layers composed of the monomeric surfactant cetylammonium chloride and the co-polymer did not display a high load bearing capacity. 44 We also note that the load bearing capacity of lubricin was significantly higher on COMP-coated PMMA compared to when lubricin was adsorbed directly on PMMA (see Fig. 8), whereas layer-by-layer deposition of DPPC and hyaluronan reduced the load bearing capacity compared to DPPC alone.…”
Section: Load Bearing Capacitymentioning
confidence: 61%
“…Drummond and co-workers have explored this in some detail, using surfactants that adsorb onto the substrate surface mixed with a diblock copolymer to modify the lubrication performance. 44,48,79,80 In their initial studies, using a double-chained surfactant which in itself provided low friction and high load bearing capacity, it was found that coadsorption of a hydrophobically end-modified poly(ethylene oxide) compromised the lubrication performance. 48 In later studies oligomeric cationic surfactants were utilized, and the layers formed by these surfactants alone had relatively low load bearing capacity.…”
Section: Load Bearing Capacitymentioning
confidence: 99%
“…Previous studies have shown that crosslinking of the adsorbed polymer layer is more often related to increased friction forces, despite the improvement in wear resistance. 43,44,46,47,49,50,52 However, the crosslinked PGMchitosan layers in this study show both lower friction forces 45 and improved wear resistance. According to Fig.…”
mentioning
confidence: 65%
“…Mikhail and Alexander prepared an aerosol dust suppressant using urea, KCl, and NaHCO 3 as raw materials that can effectively inhibit the explosion of oil, gas, and dust . Drummond and coworkers used composites of surfactants to achieve the optimum wetting ratio in the application to dust prevention . Tan et al .…”
Section: Introductionmentioning
confidence: 99%
“…12 Drummond and coworkers used composites of surfactants to achieve the optimum wetting ratio in the application to dust prevention. 13 Tan et al made a dust suppressant with good adhesion and strong pavement performance by combining soluble starch, sodium silicate, and glycerol. 14 Although the abovementioned dust suppressants have good adhesion and good dust suppressing effects, the process of coal transportation and storage is often accompanied by extremely bad weather.…”
Section: Introductionmentioning
confidence: 99%